Lazer, animação sociocultural e educação profissional: mapeamento de currículos-encontros no Brasil e em Portugal - Adriano Gonçalves da Silva (2021)
This thesis is supported by my encounters with public education, teaching, professional education, leisure, and cultural studies. Based on the understanding that the curricular guidelines present similarities between technical training in leisure in Brazil and in socio-cultural animation in Portugal, I seek support in post-critical curriculum theories to understand how the curricula of these formations are constituted in their contexts. The comprehension that teachers are codifiers of these curricula, constituting them and being constituted by them, led me to question: how are these curricula composed? Which encounters are made possible by them? What disputes are present? How did teachers get involved and was involved in the composition of these curricula? How do they negotiate with the speeches about leisure and sociocultural animation that cross curricular practices? Thus, the objective of this study was to analyze, in the light of the teaching discourses, how the curriculum of one technical course in leisure in Brazil and one of a sociocultural animator course in Portugal are constitute. I defined as a methodological strategy for this study, the understanding of curricula from the discourse teachers of technical subject, in dialogue with the national and local norms that intend to regulate them. To this end, I looked for a public secondary school that would offer the sociocultural animator course with double certification in Portugal and a public secondary school that would offer the technical course in leisure with integrated curricular in Brazil. Having defined the schools with which I would work, I started the data production process, which involved an entry phase in the field with exploratory interviews with the coordinators of the courses, followed by interviews with the teachers and data analysis. The teachers’ speeches took me to the processes of subjectivity present in educational policies, institutional practices and ways of conceiving and producing what it means to be a teacher of the technical course in leisure at the Federal Institute of São Paulo and the professional course of sociocultural animator of the Group of Schools Coelho e Castro. The curricula in the form that are presented and materialized in the professional courses dialog with the confrontations experienced by the field of leisure and sociocultural animation, with its struggles for authenticity and disciplinary identities and the tensions between leisure and recreation, and between social and cultural animation. In their socioeconomic assemblages, these curricula assume commitments to training to work in the labor market, work in the context of training, preparation for higher education, training for life and the realization of the social role of the school. Thus, I consider that the curricula-encounters studied provide reflections on professional training in leisure, in sociocultural animation and the relationships between these training processes.